Breath-hold times in patients undergoing radiological examinations - Groell, Reinhard (Radiology and oncology (Ljubljana), 2001)
Background: Breath-holding is necessary for imaging studies of the thorax and abdomen using computed tomography, magnetic resonance imaging or ultrasound examinations. The purpose of this study was to compare the breath-hold times in expiration and inspiration and to evaluate the effects of hyperventilation.Patients and methods. Thirty patients and 19 healthy volunteers participated in this study after informed consent was obtained in all. The breath-hold times were measured in expiration and inspiration before and after hyperventilation. Results. The mean breath-hold times in expiration (patients: 24+-9sec, volunteers: 27+-7sec) were significantly shorter than those in inspiration (patients: 41+-20sec, p-0.005) of the mean breathhold times either in expiration and in inspiration and for both patients and volunteers. Conclusions. Althoughbreath-holding in expiration is recommended for various imaging studies particularly of the thorax and of the abdomen, suspending respiration in inspiration enables the patient a considerable longer breath-hold time.
Keywords: Breath tests; dihanje; Heart failure, congestive; hiperventilacija; Hyperventilation; Lung diseases, obstructive; Magnetic resonance imaging; radiologija; slikovna diagnostika; Thorax; Tomography, x-ray computed; Ultrasonography; zadrževanje diha